2011
DOI: 10.4067/s0717-95022011000400012
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Tongue of Reptilian Species Psammophis sibilans, Tarentola annularis and Crocodylus niloticus

Abstract: SUMMARY:Three different reptilian species Psammophis sibilans (Order Ophidia), Tarentola annularis (Order Squamata and Crocodylus niloticus (Order Crocodylia) are used in the present study. Their tongue is removed and examined morphologically. Their lingual mucosa examined under scanning electron microscopy (SEM) as well as processed for histological investigation. Gross morphological studies revealed variations of tongue gross structure being elongated with bifurcated end in P. sibilans or triangular flattene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
3
10
1
Order By: Relevance
“…A deep bifurcation was reported in snakes and varanids [32][33][34][35]. Similar structural pattern of forked tongue was reported by [36] in Python molurus.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…A deep bifurcation was reported in snakes and varanids [32][33][34][35]. Similar structural pattern of forked tongue was reported by [36] in Python molurus.…”
Section: Discussionsupporting
confidence: 66%
“…Similar glands are found in E. Schneideri [17], terrestrial tortoises [19], iguanid lizard O. cuvieri [21], Sphenodon [25] and in Acanthodactylus boskianus [56]. The secretion of large amounts of mucus acts as a lubricant that facilitates food movements, transport and swallowing [19,35,56,57].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Reptiles generally have taste buds in the lingual epithelium, which is coincident with S. tsinlingensis, and the same structure can also be found in Psammophis sibilans, Tarentola annularis and Crocodylus niloticus (El-Sayyad et al, 2011). In addition, Crocodilians generally have taste buds in the oral epithelium and lingual epithelium (Ferguson, 1981), and some Testudines have taste buds in the oropharyngeal mucosa (Iwasaki and Kumakura, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…This agrees with Herrel et al (2001) who described that the bifurcation was almost absent in chameleons. However, de Groot et al (2004) in Python molurus, El-Sayyad et al (2011) in Psammophis sibilans, and Darwish (2012) in ptyodactylus guttatus and Stenodactylus petrii (Lacertilia, Gekkonidae), reported that the apex is bifurcated.…”
Section: Discussionmentioning
confidence: 99%